2015
DOI: 10.1039/c4ra16168h
|View full text |Cite
|
Sign up to set email alerts
|

Expanding applications of zeolite imidazolate frameworks in catalysis: synthesis of quinazolines using ZIF-67 as an efficient heterogeneous catalyst

Abstract: A cobalt zeolite imidazolate framework (ZIF-67) was successfully synthesized and characterized by several techniques. The ZIF-67 was used as an efficient heterogeneous catalyst for the cyclization reaction of 2aminobenzoketones and benzylamine derivatives to form quinazoline products. The optimal conditions involved the use of TBHP oxidant in toluene solvent at 80 C. Remarkably, the ZIF-67 catalyst exhibited better performance in the cyclization reaction than common cobalt salts such as Co(NO 3 ) 2 , CoCl 2 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(32 citation statements)
references
References 63 publications
2
29
0
1
Order By: Relevance
“…ZIFs possess the unique properties of high crystallinity, large surface area, exceptional chemical and functional tunability. As a result, ZIFs have gained considerable attention for their potential application in gas storage 2 , CO 2 capture 3,4 , separation 5,6 , sensing 7 , catalysis 8 , drug delivery 9,10 and water treatment 11,12 . Zeolitic imidazolate framework-8 (ZIF-8), with sodalite (SOD) topology constructed from Zn and Hmim, is one of the most investigated ZIF materials 1315 .…”
Section: Introductionmentioning
confidence: 99%
“…ZIFs possess the unique properties of high crystallinity, large surface area, exceptional chemical and functional tunability. As a result, ZIFs have gained considerable attention for their potential application in gas storage 2 , CO 2 capture 3,4 , separation 5,6 , sensing 7 , catalysis 8 , drug delivery 9,10 and water treatment 11,12 . Zeolitic imidazolate framework-8 (ZIF-8), with sodalite (SOD) topology constructed from Zn and Hmim, is one of the most investigated ZIF materials 1315 .…”
Section: Introductionmentioning
confidence: 99%
“…Figure a showed the XRD patterns of the above three samples. The main characteristic peaks of bare ZIF‐67 NPs matched well with those reported in the literature ,,, Some typical characteristic peaks of the XRD pattern for ZIF‐67 CMs were matched well with that of as synthesized ZIF‐67NPs.…”
Section: Resultsmentioning
confidence: 99%
“…ZIFs often possess unique properties of the microporosity, crystallinity, high specific surface areas, and high chemical and thermal stability, compared with other types of metal‐organic frameworks . Recently, ZIFs has attracted great attention in diverse applications, including liquid adsorption,, catalysis, and chemical analysis ,. It is reported that ZIFs can be used as adsorbents to absorb contaminants in water, such as dyes,, heavy metals salts,, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other types of MOFs, ZIFs often exhibit unique properties of the microporosity, crystallinity, high surface area, and high chemical and thermal stability [4][5][6][7][8]. Recently, ZIFs has attracted considerable attention in diverse applications, including liquid adsorption [9,10], catalysis [11][12][13], and chemical analysis [14,15]. It has reported that ZIF-67 has been as an efficient heterogeneous catalyst for the cyclization reaction of 2-aminobenzoketones and benzylamine derivatives to form quinazoline products [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ZIFs has attracted considerable attention in diverse applications, including liquid adsorption [9,10], catalysis [11][12][13], and chemical analysis [14,15]. It has reported that ZIF-67 has been as an efficient heterogeneous catalyst for the cyclization reaction of 2-aminobenzoketones and benzylamine derivatives to form quinazoline products [13]. In addition, ZIF-67 was found to adsorptive remove phenol from aqueous system [16].…”
Section: Introductionmentioning
confidence: 99%